Suppression of BMP signaling by PHD2 deficiency in Pulmonary Arterial hypertension. (23rd March 2022) - Liu, Bin; Yi, Dan; Pan, Jiakai; Dai, Jingbo; Zhu, Maggie M.; Zhao, You‐Yang; Oh, S. Paul; Fallon, Michael B.; Dai, Zhiyu
Abstract: BMP signaling deficiency is evident in the lungs of patients with pulmonary arterial hypertension. We demonstrated that PHD2 deficiency suppresses BMP signaling in the lung endothelial cells, suggesting the novel mechanisms of dysregulated BMP signaling in the development of pulmonary arterial hypertension.